The Effect of Poplar PsnGS1.2 Overexpression on Growth, Secondary Cell Wall, and Fiber Characteristics in Tobacco - Lu, Tingting; Liu, Lulu; Wei, Minjing; Liu, Yingying; Qu, Zianshang; Yang, Chuanping; Wei, Hairong; Wei, Zhigang (Frontiers in Plant Science, 2018)
The glutamine synthetase (GS1) is a key enzyme that catalyzes the reaction of glutamate and ammonia to produce glutamine in the nitrogen metabolism. Previous studies on GS1s in several plant species suggest that overexpression of GS1s can enhance N utilization, accelerate plant vegetative growth, and change wood formation. In this study, we isolated a GS1 gene, termed PsnGS1.2, from Populus simonii×Populus nigra. This gene was expressed at a higher level in roots, and relatively lower but detectable levels in xylem, leaves and phloem of P. simonii × P. nigra. The protein encoded by PsnGS1.2 is primarily located in the cytoplasm. Overexpression of PsnGS1.2 in tobacco led to the increased GS1 activity and IAA content, the augmented nitrogen assimilation, and the enlarged leaves with altered anatomical structures. These changes presumably promoted photosynthetic, growth, and biomass productivity. It was noteworthy that the secondary cell walls and fibre characteristics changed remarkably in PsnGS1.2 transgenic tobacco. These changes aligned well with the altered expression levels of the genes involved in fibre development, secondary cell wall component biosynthesis, IAA biosynthesis, amino acid transport, and starch breakdown. Taken together, the results from our study suggest that catalytic functions of PsnGS1.2 on nitrogen assimilation and metabolism in transgenic tobacco had significant effects on vegetative growth, leaf development, and secondary cell wall formation and properties through acceleration of photosynthesis and IAA biosynthesis, and redirection of carbon flux to synthesis of more cellulose and hemicellulose.